Variability in healthcare delivery: It is never a good thing. Issue 3 (9th September 2022) - Butman, Samuel M.
Abstract: In medicine, wide variations in healthcare delivery or outcomes are a sign of missing information and beg for more information in a timely resolution. While differences in patient selection for intervention in out‐of‐hospital‐cardiac‐arrest in Wales and England might seem regional, there is little reason to assume this is not true across many other geographical areas.